2017
DOI: 10.1159/000481356
|View full text |Cite
|
Sign up to set email alerts
|

Structural Pulmonary Abnormalities Still Evident in Schoolchildren with New Bronchopulmonary Dysplasia

Abstract: Background: A new pattern of bronchopulmonary dysplasia (BPD) has emerged with the improved survival of preterm children. Objectives: Our aim was to characterize structural abnormalities associated with new BPD and to evaluate whether the severity of high-resolution computed tomography (HRCT) changes is associated with lung function. Methods: HRCT scans were performed on 21 schoolchildren with a history of new BPD (mild, n = 9; moderate, n = 4; and severe, n = 8) with a mean age of 12.7 years (range: 8.7-16.7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(77 reference statements)
2
12
0
1
Order By: Relevance
“…The incidence of BPD in extremely preterm neonates was reported to be as high as 68% (5). The disruption of normal pulmonary vascular and alveolar growth after early birth subjects these infants to increased cardiopulmonary morbidity and mortality (6,7). Currently, with the improvement of intensive care interventions, the mortality rate of extremely preterm neonates with BPD has decreased (7-9).…”
Section: Clinical Trial Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of BPD in extremely preterm neonates was reported to be as high as 68% (5). The disruption of normal pulmonary vascular and alveolar growth after early birth subjects these infants to increased cardiopulmonary morbidity and mortality (6,7). Currently, with the improvement of intensive care interventions, the mortality rate of extremely preterm neonates with BPD has decreased (7-9).…”
Section: Clinical Trial Registrationmentioning
confidence: 99%
“…Currently, with the improvement of intensive care interventions, the mortality rate of extremely preterm neonates with BPD has decreased (7-9). However, many survivors still face a lifetime of disability, including long time dependence of oxygen therapy, asthma, and repeated hospital admission because of pneumonia even in developed countries (4,6). Although new ventilation strategies and pharmacological treatments have been applied, there are no curative therapies available to target the underlying structural changes of the lungs leading to the symptoms (3).…”
Section: Clinical Trial Registrationmentioning
confidence: 99%
“…The IOS ndings of increased resistance of central and peripheral airways, lower reactance and increased AX and Fres suggest that children born preterm may have an increase in airway tone particularly in peripheral airways. Imaging studies performed in school children born very preterm revealed structural lung abnormalities of the peripheral airways such as airway wall thickening, increased subpleural opacities (that usually stand for alveolar septal brosis), mosaic perfusion and air trapping both in children with BPD 31 and in children without BPD 8 suggesting a xed peripheral airway narrowing 32 . These changes might be present especially in children who might have suffered from anatomical damages during fetal life like those with intrauterine growth restriction (IUGR).…”
Section: Populationmentioning
confidence: 99%
“…Review of the evidence addressing the question on lung imaging PICO 1In children with BPD, does monitoring with lung imaging versus no lung imaging affect important and critical defined outcomes?Summary of the evidenceNo direct evidence that would answer this question in an appropriate way was identified. Indirect evidence was provided by four studies that examined the relationship of lung imaging with lung function or duration of supplemental oxygen need (supplementary table S3.1)[47][48][49][50]. 21 school-children with BPD (mild n=9, moderate n=4, severe n=8) were offered the opportunity to undergo high-resolution CT (HRCT) scans[47].…”
mentioning
confidence: 99%
“…Indirect evidence was provided by four studies that examined the relationship of lung imaging with lung function or duration of supplemental oxygen need (supplementary table S3.1)[47][48][49][50]. 21 school-children with BPD (mild n=9, moderate n=4, severe n=8) were offered the opportunity to undergo high-resolution CT (HRCT) scans[47]. The rate of severe BPD was higher compared to those not participating in scanning.…”
mentioning
confidence: 99%